From social justice to Islamic revivalism: an interrogation of Sayyid Qutb's discourse (2012)
While Sayyid Qutb is an acclaimed Islamist and leader of the Muslim Brotherhood in Egypt, that he has not been fully understood is confirmed by the persistent view that he laid the foundation for the prevailing ‘Islamic terror and Islamist fundamentalism’ all over the globe. Though there is a panoply of works that have attempted to explain and clarify this misunderstanding of Qutb’s Islamic revivalism and reformism through a study of his writings and works yet the argument that his Islamic revivalism added to his zeal for rejecting modernity, leading to ‘Islamic terror and Islamist fundamentalism’ leaves some questions such as how did he move from a pure social justice crusader to an Islamist, why did he hate America, does his work provide inspiration for Islamic militancy, fundamentalism and terrorism etc and did his childhood upbringing, education, works and Islamic revivalism give insight into the so-called phenomenon of ‘Islamic terrorism still begging for answers. This paper is premised on the argument that Qutb, as a true African, despite his critical analysis and condemnation of the West and in fact all Muslim societies which he terms Jahili Societies was totally opposed to all acts of terrorism as well as irrational and extreme interpretation of Islamic fundamentals as revealed in his revivalist and reformist works, especially Fi Zilal al-Qur’an, which are still inspiring Muslims, especially his views on the rights of Muslim women and their place in modern society.